Experimental Investigation on Toughness of SFRC and Bond Behavior with Reinforcing Bars - Hongmei Zhang; Zizhao Tang; Jinguang Li; Zheming Hu; Qian Feng (Buildings)
Steel-fiber reinforced concrete (SFRC) has the advantages of high strength, durability, and crack prevention ability. Studies on the compressive strength, tensile strength and flexural behavior of SFRC have been carried out by many researchers. In this paper, the toughness of SFRC along with the bond behavior between SFRC and reinforcement were investigated. Hooked-end and straight steel fibers were chosen in the toughness tests of SFRC. The test results show that the SFRC mixtures with hooked-end steel fibers exhibit higher toughness. In addition, hooked-end steel fibers were chosen to be mixed in the SFRC to demonstrate the bond behavior between SFRC and reinforcing bars. Different embedment lengths were considered in the tests to show the influence of the anchorage area on the bond–slip responses in the pull-out tests. The failure modes for different specimens were exhibited. The results show that the embedment length more than 5 times the bar diameter causes tensile failure of the reinforcement, while the embedment length of 3 times the bar diameter causes pull-out failure of the reinforcement.